The Impact of Pesticides Use on Farmer Health and Environment - Hargianti Dini Iswandari; Ari Dina Permana Citra; Okti TD Retnaningrum; Sigit Sugiharto; Chusnul Zulaika (Diponegoro University, 2020)
Pesticides are supporting component in agricultural sector. However, the excessive use of pesticides can have negative impacts on the health of farmers and the environment. This research was conducted in Kebonagung village, Sumowono sub-district to determine the impact of pesticides on health and the environment. The study population was vegetable farmers in Kebonagung Village, Sumowono District. The sample selection technique used purposive sampling method. In-depth interviews were conducted with 10 vegetable farmers and data triangulation was obtained through interviews with the Village Head of Kebon Agung. The results showed that farmers' knowledge was still lacking, farmers did not have awareness of the importance of using personal protective equipment when applying pesticides, pesticide control was carried out once every 6 months but not all farmers received this supervision. The impact of pesticides on health and the environment in Kebonagung village is still relatively light but there are indicators of an imbalance in the ecosystem due to excessive use of pesticides